KOMITE AUDIT UNTUK MENINGKATKAN TATA KELOLA PEMERINTAHAN DAN PENYAJIAN LAPORAN KEUANGAN DALAM RANGKA PENINGKATAN KINERJA PEMERINTAH DAERAH (STUDI KASUS PEMERINTAH DAERAH KABUPATEN BELITUNG) - Alexander Ikhsan; Antar MT Sianturi (Jurnal Magister Akuntansi Trisakti, 2014)
This research is a qualitative descriptive study entitled “Audit Committee to Improve Governance and Financial Statement in order to Improved Performance of Local Government (Case Study of District Government Belitung)”. The purpose of this study was to determine how much influence of the audit committee in the local government in order to improve governance and the quality of local government financial statement, and its associations with local government performance. Measuring the importance of the audit committee, which was measured using interviews with 15 respondents who have an influence on governance in the Belitung District Based on these results, we can conclude that audit committees in local government will improve the governance and the quality of local government financial statements presentation. And from the results of this study also found that the good governance and quality of local government financial statements presentation will improve the overall local government performance